Strategi Persaingan Industri Dan Substitusi Industri Impor Tehadap Kemajuan Teknologi - Tohonan Rohani Silaban; Muhammad Yasin (Jurnal Riset dan Inovasi Manajemen, 2023)
This research aims to increase knowledge and insight in the field of industrial economics and aims to analyze industrial competitive strategies in facing technological advances. The research method uses qualitative methods and library research. The data collection technique is to record important information in carrying out data analysis by means of data reduction, data presentation and drawing conclusions to obtain conclusions. The results of the research show that Indonesia's industrial strategy is to be able to survive in competition and import substitution must be increased to meet the needs of a growing society. increasing even though industry can be one of the strategies in the industrial sector that can be developed in the future in an effort to realize Indonesia's economic growth.